Environmental licensing in the wine industry: A case study for the implementation and discharge of effluents from a treatment plant - Piletti , Graziela; Maffessoni , Daiana (Seven Editora, 2023)
Environmental licensing is a management instrument established by the National Environmental Policy. An environmental license authorizes the location, construction, installation, expansion, modification, and operation of projects and activities considered effectively or potentially polluting. The wine industries have a high pollution potential within the environmental licensing process, being characterized by water consumption in several stages, generating a large volume of wastewater. This work aimed to present the environmental licensing procedures applied for the implementation of a wastewater treatment plant (WTP) in a winery in operation, in Rio Grande do Sul, Brazil. Also, was evaluated the alternatives regarding the destination for the treated wastewater. For the implementation of the WTP, the company obtained the following licenses: Preliminary Expansion License (PEL), Expansion Installation License (EIL), and Operation License Update (OLU). Due to the problem of the river flow, the alternatives described in FEPAM Technical Guideline number 005/2017 were analyzed for the disposal and reuse of treated effluents. WTP quality parameters were obtained. Following each environmental licensing procedure is essential for planning the implementation of a potentially polluting activity, to define the best alternative to minimize and mitigate all possible environmental damage. DOI:https://doi.org/10.56238/interdiinovationscrese-056